Power System SCADA and Smart Grids - Thomas, Mini S.; McDonald, John D. 1951- (CRC Press, 2015)
Power System SCADA and Smart Grids brings together in one concise volume the fundamentals and possible application functions of power system supervisory control and data acquisition (SCADA). The text begins by providing an overview of SCADA systems, evolution, and use in power systems and the data acquisition process. It then describes the components of SCADA systems, from the legacy remote terminal units (RTUs) to the latest intelligent electronic devices (IEDs), data concentrators, and master stations, as well as:Examines the building and practical implementation of different SCADA systemsOffers a comprehensive discussion of the data communication, protocols, and media usageCovers substation automation (SA), which forms the basis for transmission, distribution, and customer automationAddresses distribution automation and distribution management systems (DA/DMS) and energy management systems (EMS) for transmission control centersDiscusses smart distribution, smart transmission, and smart grid solutions such as smart homes with home energy management systems (HEMs), plugged hybrid electric vehicles, and morePower System SCADA and Smart Grids is designed to assist electrical engineering students, researchers, and practitioners alike in acquiring a solid understanding of SCADA systems and application functions in generation, transmission, and distribution systems, which are evolving day by day, to help them adapt to new challenges effortlessly. The book reveals the inner secrets of SCADA systems, unveils the potential of the smart grid, and inspires more minds to get involved in the development process